IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN FACILITIES TO IMPROVE INSTITUTION QUALITY SCHOOL - Poetri Leharia Pakpahan; Wiji Hidayati (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
One of the improvements in the quality of education is the fulfillment of the needs for facilities and adequate, quality, and ready-to-use educational infrastructure. So as for the impact of the lack of proper infrastructure of school institutions, namely that it can reduce student achievement in learning activities, especially in class. Therefore, to improve the quality of education in schools, management of facilities and infrastructure is needed to meet the needs of the student learning process at school. This study aims to determine the implementation of total quality management in improving the quality of infrastructure in schools. This research using library research with analytical study methods (library research), namely research carried out using a library alias literature, either in the form of notes, books, journals, or reports of previous research results. The analytical study used is content analytical and analytical descriptions of total quality management to improve infrastructure at school. The results of this study indicate that the facilities and infrastructure at the school are inadequate standards. Therefore, the use of infrastructure in the learning process must also be improved, as an increase in service quality continuously meets the reality and expectations for customers.